Analisis nilai karakter peduli sosial pada kartun upin-ipin season 16 episode temanku susanti dalam menunjang pendidikan karakter peduli sosial pada siswa kelas III SD - Ahmad Laththuv Majid; Rukayah Rukayah; Sandra Bayu Kurniawan (Universitas Sebelas Maret, 2025)
This study aims to describe the value of social care characters contained in Upin-Ipin cartoons in supporting the implementation of social care character education in SD Negeri Jajar Surakarta. This research is qualitative descriptive research. The subject of the study was the cartoon Upin-Ipin season 16 episode